CRISPR/Cas9 Genome editing in Pyrrhocoris apterus - Bertolutti, Maly (Jihočeská univerzita, 2020)
The CRISPR/Cas9 technology is a cutting edge method to genetically modify specific targets in the genome, which allows to create mutants in non-model organisms. The aim of this project was to genetically modify the Pyrrhocoris apterus genomic sequence of the cryptochrome2 gene using the CRISPR/Cas9 technology. Specifically, this project aimed to create a mutant with removed or modified C-terminal part of the CRY2 protein, which should later allow for studying the role of this sequence in CRY2 function.
CRISPR/Cas9 Genome editing in Pyrrhocoris apterus
Keywords: genome editing; Pyrrhocoris apterus; CRISPR technology; CRISPR/Cas9; CRY2; cryptochrome; chryptochrome gene; ciradian clock; photoperiodic clock; entomology; genome editing; Pyrrhocoris apterus; CRISPR technology; CRISPR/Cas9; CRY2; cryptochrome; chryptochrome gene; ciradian clock; photoperiodic clock; entomology